Multicenter Outcome of Hematopoietic Stem Cell Transplantation for Primary Immune Deficiency Disorders in India - Raj, Revathi; Aboobacker, Fouzia N.; Yadav, Satya Prakash; Uppuluri, Ramya; Bhat, Sunil; Choudhry, Dharma; Dua, Vikas; Kharya, Gaurav; Rastogi, Neha; Sachdev, Mansi; Khandelwal, Vipin; Swaminathan, Venkateswaran; et al. (Frontiers in Immunology, 2021)
Abstract Background: Hematopoietic stem cell transplantation (HSCT) is the curative option for many primary immune deficiency disorders (PID). In the last five years, increased awareness, availability of diagnostics based on flow cytometry, genetic testing, improved supportive care, use of reduced toxicity conditioning and success of haploidentical donor HSCT have improved access to HSCT for children with PID in India. We present results on children with PID who underwent HSCT across India and the factors that influenced outcome. Patients and Methods: We collected retrospective data on the outcome of HSCT for PID from 7 centers. We analyzed the impact of the type of PID, conditioning regimen, time period of HSCT- before or after January 2016, graft versus host disease prophylaxis, cause of mortality and overall survival. Results: A total of 228 children underwent HSCT for PID at a median age of 12 months (range 1 to 220 months) with a median follow up of 14.4 months. Infants accounted for 51.3% of the cohort and the male female ratio was 3:1. SCID (25%) and HLH (25%) were the more frequent diagnoses. Matched family donor was available in 36.4% and 44.3% children had a haploidentical HSCT. Reduced and myeloablative conditioning regimens were used with 64% children receiving a treosulfan based conditioning regimen. Peripheral blood stem cells were the predominant graft source at 69.3%. The survival in infants (60.2%) was inferior to children aged over 1 year (75.7% p value 0.01). Children with Wiskott Aldrich Syndrome (74.3%) and chronic granulomatous disease (82.6%) had the best outcomes. The survival was superior in children receiving HSCT from a matched sibling (78%) versus an alternate donor HSCT (61% p value 0.04). In the cohort transplanted after January 2016 survival improved from 26.8% to 77.5% (p value 0.00). Infection remains the main cause of mortality at in over 50% children. The 5 year overall survival rate was 68%. Conclusion: Survival of children with PID undergoing HSCT in India has improved dramatically in last 5 years. Alternate donor HSCT is now feasible and has made a therapeutic option accessible to all children with PID.